The Role of E-Learning Platforms in Transforming Teaching and Learning Practices - Deni Alfianto; Abd. Rajab (Generasi Sains Indonesia, 2025)
This study explores the role of e-learning platforms in transforming teaching and learning practices in higher education. Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis involving lecturers and students from three Indonesian universities. The findings reveal four major themes: transformation of lecturers’ roles, enhancement of student autonomy, dynamics of digital interaction, and challenges of access and digital literacy. E-learning has shifted lecturers from knowledge transmitters to facilitators, encouraged students’ self-directed learning, and created new spaces for synchronous and asynchronous interaction. However, the study also highlights persistent barriers, such as limited technological infrastructure, uneven digital literacy, and difficulties in maintaining learning motivation. These findings suggest that the transformative potential of e-learning is not merely technological but deeply pedagogical and contextual. Therefore, successful integration of e-learning requires institutional support, equitable digital access, and thoughtful instructional design to ensure meaningful engagement and sustainable learning outcomes. This research contributes to ongoing debates on digital pedagogy by showing that e-learning is both an opportunity for innovation and a challenge of digital equity in contemporary education.